Systemic effect of mineral aggregate-based cements: histopathological analysis in rats - Lucas da Fonseca Roberti Garcia; Claudia Huck; Fernando Augusto Cintra Magalhães; Pedro Paulo Chaves de Souza; Carlos Alberto de Souza Costa
Abstract Objective: Several studies reported the local tissue reaction caused by mineral aggregate-based cements. However, few studies have investigated the systemic effects promoted by these cements on liver and kidney when directly applied to connective tissue. The purpose of this in vivo study was to investigate the systemic effect of mineral aggregate-based cements on the livers and kidneys of rats. Material and Methods: Samples of Mineral Trioxide Aggregate (MTA) and a calcium aluminate-based cement (EndoBinder) containing different radiopacifiers were implanted into the dorsum of 40 rats. After 7 and 30 d, samples of subcutaneous, liver and kidney tissues were submitted to histopathological analysis. A score (0-3) was used to grade the inflammatory reaction. Blood samples were collected to evaluate changes in hepatic and renal functions of animals. Results: The moderate inflammatory reaction (2) observed for 7 d in the subcutaneous tissue decreased with time for all cements. The thickness of inflammatory capsules also presented a significant decrease with time (P<.05). Systemically, all cements caused adverse inflammatory reactions in the liver and kidney, being more evident for MTA, persisting until the end of the analysis. Liver functions increased significantly for MTA during 30 d (P<.05). Conclusion: The different cements induced to a locally limited inflammatory reaction. However, from the systemic point of view, the cements promoted significant inflammatory reactions in the liver and kidney. For MTA, the reactions were more accentuated.